Hypoxia Predicts Lower Respiratory Tract Diseases in Adults Living at High Altitudes - Leon-Abarca, Juan Alonso (2019)
Background: At sea level, tachypnea (respiratory rate> 24 / min) is a factor commonly associated with community-acquired pneumonia. However, in high altitudes, it must achieve higher rates, thus there is a need to look for other early predictors at these settings. Objective: This study aims to explore the presence of hypoxemia associated to the presence of diseases of the lower airways or not according to pulse oximetry readings. Methods: We used a database of 205071 18 to 65 year old altitude-resident outpatient adults in Cajamarca, Peru (2750 masl) as part of a private health program. Data was collected corresponding to demographic characteristics, vital functions (including peripheral oxygen saturation, SpO2) and individual diagnosis according to ICD-10 classification. The patients were divided into two groups according to the SpO2 level of 90% detected through a portable pulse oximeter. We used the Student’s T, the Mann-Whitney U test, logistic regression and proportions test for the analysis of means and differences in prevalence of diseases. The Stata 14.0 program was used for statistical analysis. Results: Diseases corresponding to the respiratory system were more common in patients with a SpO2 <90% (35.21% vs 32.11%, p <0.05). Of these patients, diseases of the lower tract were more common (2.72% vs 1.95%, p <0.05). These patients did not differ with age, heart rate, respiratory rate, blood pressure and temperature. Logistic regression shows that people with lower than 90% SpO2 are at a 40.7% higher risk of having lower respiratory tract infections (OR 1.407, 95%CI 1.26-1.56 p<0.0001). Conclusion: According to the results, high altitude adult residents who present to an outpatient clinic with an SpO2 <90% have a higher chance of presenting diseases of the lower respiratory tract, especially infections, supporting the use of pulse oximetry at high altitude outpatient settings as an early predictor of pneumonia.